Functional Outcomes of Bilateral Reverse Total Shoulder Arthroplasty: A Systematic Review - Malahias, Michael-Alexander; Brilakis, Emmanouil; Chytas, Dimitrios; Gerogiannis, Dimitrios; Avramidis, Grigorios; Antonogiannakis, Emmanouil (Joints, 2019)
Purpose To answer the question whether bilateral reverse total shoulder arthroplasty (RTSA) is a safe and effective treatment which results in satisfactory clinical and functional outcomes with low complications rates. A second question to be answered was: what is the quality of the evidence of the already published studies which investigate the use of bilateral RTSA?Methods Two reviewers independently conducted a systematic search according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses using the MEDLINE/PubMed database and the Cochrane Database of Systematic Reviews. These databases were queried with the terms “reverse” AND “total” AND “shoulder” AND “arthroplasty” AND “clinical.” Descriptive statistics were used to summarize the data.Results From the 394 initial studies we finally selected and assessed 6 clinical studies which were eligible to our inclusion–exclusion criteria. The aforementioned studies included in total 203 patients (69% females; mean age range: 67.1–75 years; mean follow-up range: 12–61 months). From those, 168 patients underwent staged bilateral RTSA (mean duration between first and second operation range: 8–21.6 months) and the rest of them a unilateral RTSA as controlled treatment. Almost all mean clinical and functional scores, which were used to assess the therapeutic value of bilateral RTSA, depicted significant postoperative improvement in comparison with the mean preoperative values. The modified Coleman methodology score, which was used to assess the quality of the studies, ranged from a minimum of 36/100 to a maximum of 55/100.Conclusion Despite the lack of high-quality evidence, staged bilateral RTSA seems to be a safe and effective procedure for patients with cuff tear arthropathy, which results in significantly improved clinical and functional outcomes and low reoperations' rates.Level of Evidence Systematic review of level III-IV therapeutic studies.
Keywords: reverse total shoulder arthroplasty; staged bilateral arthroplasty; cuff tear arthropathy; systematic review; modified Coleman score